(untitled) (Desarrollo, Estado y Espacio, 2022)
Ports are favorable locations for numerous industries. Changes in these industries and in port cargo logistics are reflected in the ways of building and inhabiting cities. This work aims to reflect on the process of urbanization of the port space in its interaction with the city within, considering four different moments. In order to limit the unit of analysis, four working-class housing neighborhoods were selected taking into account their origin associated with the construction industries of the Port of La Plata, the refrigerators and the YPF distillation plant. The result of the analysis was raised on two scales, the first describing the relationship of each neighborhood with the port, urban and industrial territory, and the second describing the logic of internal relationships within the neighborhoods. The growth logic of the port responds to that of the global economy, while neighborhood growth depends on the local economy, increasing that port and city have dynamics that tend to autonomy.